Analisis Implementasi Kebijakan Badan Usaha Milik Desa (BUMDES) sebagai Pendorong Pembangunan Ekonomi di Desa Ngadirejo Slawe, Kecamatan Widang Kabupaten Tuban - Nur Mahmudah, Laila; Arlupi Utami, Dian; Indah Sahilla, Fenny; Rachmah Amaretta, Fanni; Aini, Khurotul; Candra Sari, Dewi (JPSI (Journal of Public Sector Innovations), 2023)
BUMDes is one of the programs set by the government as an effort to develop and improve the economy for village communities in order to achieve village welfare through the potential possessed by the village. One of the villages implementing the BUMDes policy is Ngadirejo Slawe Village, Widang District, Tuban Regency, East Java. The purpose of this research was to 1) describe how the BUMDes policy was implemented in Ngadirejo Slawe Village 2) describe the factors influencing the management of BUMDes in Ngadirejo Slawe Village. This study uses a type of qualitative research method with data collection techniques in the form of interviews, observation and documentation. The results of this study indicate that the implementation of the BUMDes policy in Ngadirejo Slawe Village has gone well even though it often encounters obstacles in the BUMDes management process, but BUMDes employees in Ngadirejo Slawe Village always try to provide services to the people of Ngadirejo Slawe Village optimally according to their needs. On the other hand, BUMDes Ngadirejo Slawe has the support of 4 farmer groups (Poktan), 9 working groups (Pokja), and 3 workers from the main diesel as a support for service infrastructure on community agricultural land in Ngadirejo Slawe Village.